2022
DOI: 10.1039/d2cp02779h
|View full text |Cite
|
Sign up to set email alerts
|

Doping atom improves photocatalytic performance in a new metal-free organic photocatalyst for water splitting

Abstract: Photocatalytic water splitting for hydrogen is an ideal technology in produce new energy by solar energy. In the process of photocatalysis, how to improve the catalytic performance of catalysts is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…As such, we studied the adsorption of Mn, Fe, Co, and Ni, and the post-adsorbed structures are referred as A-g-C 3 N 4 /C 2 N- h 2D (A = Mn, Fe, Co, Ni) nanoribbons. 47 First, we take the adsorption of Mn as an example to prove the position where the adsorption is most stable. There are two transition metal adsorption sites, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As such, we studied the adsorption of Mn, Fe, Co, and Ni, and the post-adsorbed structures are referred as A-g-C 3 N 4 /C 2 N- h 2D (A = Mn, Fe, Co, Ni) nanoribbons. 47 First, we take the adsorption of Mn as an example to prove the position where the adsorption is most stable. There are two transition metal adsorption sites, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we studied the electronic properties of X-ZN 4 NRs and analyzed their electronic properties by calculating their energy bands and DOS. 36,37 When different transition metal atoms were placed on X-ZN 4 NRs, some exciting changes occurred in their electronic properties. 38 We found that the X-ZN 4 NRs of various types have entirely different electronic properties, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For an excellent photocatalyst, the ability of harvesting sunlight, particularly visible and ultraviolet light, to give rise to electronhole pairs is crucial to water splitting. [37][38][39][40] To determine the optical absorption coefficient of the TTG, we have calculated its optical absorption spectrums that are polarized in X-direction and Z-direction of TTG, as shown in Fig. 3(d).…”
Section: Photocatalytic Behaviour Of Ttg For Overall Water Splittingmentioning
confidence: 99%